Crossover between Tilt Families and Zero Area Thermal Expansion in Hybrid Prussian Blue Analogues. Issue 50 (15th November 2017) - Phillips, Anthony E.; Fortes, A. Dominic
Abstract: Materials in the family of Prussian blue analogues (C3 H5 N2 )2 K[M (CN)6 ], where C3 H5 N2 is the imidazolium ion andM =Fe, Co, undergo two phase transitions with temperature; at low temperatures the imidazolium cations have an ordered configuration ( C 2/ c ), while in the intermediate‐ and high‐temperature phases (both previously reported as R 3 ‾ m ) they are dynamically disordered. We show from high‐resolution powder neutron diffraction data that the high‐temperature phase has zero area thermal expansion in the ab ‐plane. Supported by Landau theory and single‐crystal X‐ray diffraction data, we re‐evaluate the space group symmetry of the intermediate‐temperature phase to R 3 ‾ . This reveals that the low‐to‐intermediate temperature transition is due to competition between two different tilt patterns of the [M (CN)6 ] 3− ions. Controlling the relative stabilities of these tilt patterns offers a potential means to tune the exploitable electric behaviour that arises from motion of the imidazolium guest. Abstract : A different tilt : A reassessment of the symmetry of two cyanide‐bridged perovskite analogues reveals that phase transitions in these materials arise from competition between two different tilt patterns. Tilt engineering of the hybrid materials provides a way to access combinations of distortions that are rare or impossible among the inorganic perovskites.